HLA Associations and Clinical Implications in T-Cell Mediated Drug Hypersensitivity Reactions: An Updated Review - Chi-Yuan Cheng; Shih-Chi Su; Chi-Hua Chen; Wei-Li Chen; Shin-Tarng Deng; Wen-Hung Chung (Journal of Immunology Research, 2014)
T-cell mediated drug hypersensitivity reactions may range from mild rash to severe fatal reactions. Among them, drug reaction with eosinophilia and systemic symptoms (DRESS) or drug-induced hypersensitivity syndrome (DIHS), Stevens-Johnson syndrome/ toxic epidermal necrolysis (SJS/TEN), are some of the most life-threatening severe cutaneous adverse reactions (SCARs). Recent advances in pharmacogenetic studies show strong genetic associations between human leukocyte antigen (HLA) alleles and susceptibility to drug hypersensitivity. This review summarizes the literature on recent progresses in pharmacogenetic studies and clinical application of pharmacogenetic screening based on associations between SCARs and specific HLA alleles to avoid serious conditions associated with drug hypersensitivity.